Testicular torsion: a scrotal catastrophe - Vagholkar, Ketan; Chandrashekhar, Shantanu; Chitalia, Dhairya; Bhatnagar, Shubhi; Sibbadi, Sreyasvi (International Surgery Journal, 2019)
Testicular torsion is a serious scrotal emergency having a negative impact on fertility and in its most severe presentation, there is potential loss of the testicle if not diagnosed early. The condition needs to be diagnosed promptly with immediate surgical intervention. Intermittent testicular torsion (ITT) is a forerunner or a red flag for an impending frank testicular torsion. ITT is characterized by sudden onset of testicular pain which may resolve spontaneously before further investigation and treatment. Testicular torsion in adults is usually intravaginal in location and can be diagnosed clinically if the patient presents early with typical clinical signs. A case of ITT who presented with frank unilateral testicular torsion diagnosed clinically and surgically treated with salvage of the affected testes is presented to highlight the importance of history of ITT and typical clinical features. The anatomical aspects and pathophysiology of testicular torsion including the aftermath is discussed. ITT is a forerunner to frank testicular torsion. If offered prophylactic orchidopexy then a frank episode of testicular torsion with all its sequelae can be averted.